Derive the kinematic equations for constant a from change in x=V(avg)Xt & change in v= a(avg)Xt
(Every other equation that can be made from x=x(1)+V(0)t+.5at^2)
The Attempt at a Solution
My main problem with this problem is that I don't know exactly what it's asking and the phrasing confuses me.
But what I did was turned the change in x=V(avg)Xt into v=v(o)+at through deriving and substitution.
For the change in v= a(avg)Xt equation, I turned it into a=change in v/t through deriving and substitution.
Once again I'm not even sure that I even answered the question, can someone please interpret the question in a way I can understand it?
Thanks in advance.